IDEAL REGULATIONS OF LAW ENFORCEMENT AGAINST MEDICAL MALPRACTICE TRADITIONAL HEALTH WORKERS - Oktareza, Dwi; Yulianingrum, Aullia Vivi; Alhadi, Muhammad Nurcholis; Elviandri; Suhadi, Nainuri (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
Traditional health services in Indonesia play an important role in maintaining public health, but the increasing cases of malpractice in this practice can endanger patient safety. The main challenges are the lack of supervision and the lack of legality that exacerbate the potential for malpractice. Therefore, strict legal protection is needed to ensure that traditional medicine is safe, effective, and meets standards, as well as to protect patients and traditional health workers. This study uses a normative legal method with a legislative, conceptual, and case study approach. Data were collected through literature studies and analyzed descriptively to understand the legal protection for patients of traditional health services. This study proposes strengthening supervision of traditional health practices through the establishment of a Traditional Health Worker Supervisory Board and non-litigation dispute resolution mechanisms such as mediation or arbitration. In addition, strict law enforcement against malpractice through administrative, civil, and criminal law will increase the accountability of traditional health workers, improve the quality of services, and provide a sense of justice for patients. Thus, it is hoped that a balance will be created between preserving tradition and effective legal protection to create a safe and fair health system in Indonesia.